دراسة العلاقة بين المتغيرات الصحية والمتغيرات الاقتصادية في سورية خلال الفترة (2000-2011) (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The research aims to study the relationship between the health situation variables and a group of economic variables in Syria during the Period (2000-2011),  as the research aims to create a mathematical model that illustrates the relationship between them using Canonical Analysis. The most significant results as follows: - There is a very strong and statistically significant correlation between health level variables and economic variables. - The result of canonical analysis shows that national income per capita is the most influential variable in health-level variables, followed by total investments, and hence average per capita gross domestic product, and then the revised rate of activity. - The result of canonical analysis shows that the average population per bed and crude mortality rate have a strong impact on economic variables. - We have come to build a mathematical model that represents the relationship between health level variables and economic variables.     هدف البحث  إلى دراسة العلاقة بين متغيرات المستوى الصحي ومجموعة من المتغيرات الاقتصادية في سورية خلال الفترة (2000 – 2011)، كما هدف إلى إيجاد نموذج رياضي يوضح العلاقة بينهما باستخدام التحليل القانوني. وتمثلت أهم نتائج البحث بالآتي:   -  وجود علاقة ارتباطية قوية جداً وذات دلالة إحصائية بين متغيرات المستوى الصحي والمتغيرات الاقتصادية. -  تبين لنا نتيجة التحليل القانوني أن نصيب الفرد من الدخل القومي هو أكثر المتغيرات تأثيراً في متغيرات المستوى الصحي، يليه إجمالي الاستثمارات ، ومن ثم متوسط نصيب الفرد من الناتج الإجمالي المحلي، فمعدل النشاط المنقح. -  تبين لنا نتيجة التحليل القانوني أن لمتوسط عدد السكان لكل سرير ومعدل الوفيات الخام تأثيراً قوياً على المتغيرات الاقتصادية. -  توصلنا لبناء نموذج رياضي يمثل العلاقة بين متغيرات المستوى الصحي والمتغيرات الاقتصادية.